2005
DOI: 10.1364/opex.13.004210
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of single isolated cell nuclei using optical projection tomography

Abstract: A method is presented for imaging single isolated cell nuclei in 3D, employing computed tomographic image reconstruction. The system uses a scanning objective lens to create an extended depth-of-field (DOF) image similar to a projection or shadowgram. A microfabricated inverted v-groove allows a microcapillary tube to be rotated with sub-micron precision, and refractive index matching within 0.02 both inside and outside the tube keeps optical distortion low. Cells or bare cell nuclei are injected into the tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 22 publications
0
109
0
Order By: Relevance
“…Recent technical developments have made it possible to combine flow cytometry with CT on the cellular level, allowing for cytometry in 3 dimensions. 32 In addition, it has been demonstrated that automated cancer cell recognition based on 3-dimensional measurements is superior to 2-dimensional (slide-based) cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technical developments have made it possible to combine flow cytometry with CT on the cellular level, allowing for cytometry in 3 dimensions. 32 In addition, it has been demonstrated that automated cancer cell recognition based on 3-dimensional measurements is superior to 2-dimensional (slide-based) cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…OPT has been shown to reveal superb sectioning ability, useful for reconstructing vertebrate embryos and in the examination of the 3D anatomy of developing organs [222,224,225] (see Figure 18); modelling of early human brain development [226]; 3D imaging of isolated cell nuclei [227]. With regard to contributions this technique has made to the knowledge of flow and related dynamics, OPT has been shown to be applicable in studies of gas-solids flow to analyse particle concentration [228]; general flow rate analyses [229,230]; cell tracing [231]; and the spatiotemporal analysis of zebrafish [232].…”
Section: Optical Projection Tomographymentioning
confidence: 99%
“…The system was built on a widefield optical microscope (Olympus IX71) with a customdesigned microcapillary-based rotation stage. 25 Since OPTM can do multimodal imaging, both absorption as well as fluorescence imaging were performed on the same instrument. 26 For absorption imaging, the light from the halogen lamp (QTH) is filtered by a diffuser and a color filter.…”
Section: Feulgen Staining the Feulgen Staining Technique Was Per-mentioning
confidence: 99%
“…OPTM generates 3-D, submicron, isometric, and high-resolution images of nuclear features. 25 Since the entire volume of the nucleus is measured, there is less uncertainty in the measure of total DNA content as every voxel is used to calculate the integrated optical density. Variations in perspective of the nucleus from 2-D images are eliminated in a single OPTM image.…”
Section: Introductionmentioning
confidence: 99%